The Erotic and the Eternal: Striving for the Permanence of Meaning - Kobow, Beatrice Sasha (Conatus - Journal of Philosophy, 2021)
The paper presents three conceptions of ‘conatus’ that show the will to persist as being connected to the individual’s participating in a culture or other collective entity and which present human striving as transcending mere biological givenness. The human strife as a movement between the ‘erotic’ and, the ‘eternal’ is analyzed in three conative ‘myths’ – ‘eros’ in Plato’s Symposium, ‘cura’ in Heidegger’s Sein und Zeit, and ‘Geist’ in Scheler’s Die Stellung des Menschen im Kosmos.